Peran Guru Aqidah Akhlaq Dalam Menanamkan Nilai-Nilai Moralitas Siswa SMP Aisyiyah Curup - Siti Bandiah (STAI Terpadu Yogyakarta, 2020)
This study aims to answer the researcher's questions, yes. what is the moral condition of the students and what are the efforts of the morality teacher in instilling the values ​​of Student Morality in Aisyiyah Curup